Energy-absorbing characteristics of hollow-cylindrical hierarchical honeycomb composite tubes inspired a beetle forewing. (15th December 2021) - Duan, Y.; Zhang, T.; Zhou, J.; Xiao, H.; Chen, X.; Al Teneiji, M.; Guan, Z.W.; Cantwell, W.J.
Highlights: This paper presents the superior energy absorption capacity of hollow-cylindrical-joint hierarchical honeycomb composite tubes under axial quasi-static crushing. The fiber orientation (α) has a significant effect on the energy-absorbing characteristics of these structures and specific energy absorption (SEA) tend to initially decrease and then increase with increasing α. The SEA of the biomimetic multi-cell tubes can be significantly enhanced by employing different fiber orientations. The highest SEA value measured on these structures, 77.3 J/g, is more than double measured on a traditional circular tube (34.9 J/g). Abstract: This paper investigates the superior energy-absorbing characteristics of hollow-cylindrical-joint hierarchical honeycomb composite tubes under axial quasi-static crushing. Biomimetic multi-cell tubes (BMCTs), inspired by the forewing of a beetle, were manufactured using the vacuum bag moulding method. Quasi-static compression tests were conducted to characterize the force–displacement response, the progression of failure, the crashworthiness characteristics, and the corresponding energy absorbing mechanisms. The experimental results show that the fiber orientation (α) has a significant effect on the energy-absorbing characteristics of these structures. The crush load efficiency (CLE) and specific energy absorption (SEA) tend to initially decrease and then increase with increasing α. It has also shown that the SEA of the BMCTs can be significantly affected by employing different fiber orientations. The highest SEA value measured on these structures, 77.3 J/g, is more than double of 34.9 J/g measured on the single circular tube counterpart. The energy-absorbing capacity of the composite structures is devisable and can be enhanced by integrated biomimetic design.